RETENTION BOND AND PERFORMANCE OF CONSTRUCTION PROJECTS IN NIGERIA - Ayodeji Oke; Peter Ogunmola (Journal of Construction Project Management and Innovation)
Retention bond guarantees that the contractor will carry out all necessary work to correct structural and/or other defects discovered immediately after completion of the contract, even if full payment has been made to the contractor. This research work assesses the effects of retention bond on construction project performance in Nigerian construction industry. Cost data were collected through the distribution of sixty (60) questionnaires of which fifty-seven administered questionnaires were retrieved. Data were analysed using correlation and regression methods of analysis. The findings from the study indicated that there is a significant relationship between retention bond and construction project performance in terms of cost and time. The study recommends that professional bodies should encourage the use of retention bond in the Nigerian construction industry by sensitizing professionals of its importance which is to enable effective delivery of projects within its initial cost and time. Also, contractors should encourage their clients to always include sum to cover up for retention bond in their contract sum.